(untitled) (Health Renaissance, 2011)
Background: Child malnutrition is the single biggest contributor to under-five morbidity and mortality. Objectives: To assess the prevalence and types of malnutrition in children below 60 months of age, attending outpatient department at Nepal medical college teaching hospital in Attarkhel, Kathmandu, Nepal. Methods: A prospective study was carried out in five hundred and twelve children below 60 months of age from September 2010 to April 2011. Children detailed history, sex, weight were recorded and length/height were measured using standard technique. The length /height and weight were plotted on WHO centiles curves.1The malnutrition were graded according to WHO classification. Result: Out of 512 children, according to WHO based on weight for age assessment , 148 (28.9%) were undernourished .Subsequently, in weight for height analysis, 73 (14.2%) were wasted and in height for age assessment, 64 (12.5%) were stunted. The present study also shows , 59 (11.5%), 50 (9.80%) and 14 (2.7%) children with acute, chronic and acute on chronic malnutrition. Conclusion: This study revealed that a high prevalence of undernutrition exists in Nepalese children. Overall, 28.9% children were undernourished. Illiteracy, large family size, not exclusively breast feeding, delayed weaning and low socio- economic status are the major risk factors for malnutrition. Keywords: anthropometry; undernutrition; World Health Organization. DOI: http://dx.doi.org/10.3126/hren.v9i3.5588 HR 2011; 9(3): 184-188